O processo de municipalização do ensino em Itirapina: a experiência de uma década - Moraes, Maria da Graça Zucchi (2009)
The goal is to make an assessment of the decentralization process of the elementary school in the city of Itirapina in the State of São Paulo, making a picture of the municipal education as a whole. This process begins in August 1997, by signing the Partnership Agreement between the State Department of Education and the City of Itirapina, transferring a single state school from 1st to 4th grade in the city, manage it for this. This process begins with only one school and, gradually, after just over ten years, the growth of the municipal network is stressed, to read in 2008, four units of basic education, two of them full-time. The interest of this research work is to analyze this whole process in the ten years to understand its contradictions and identify the variables that affect positively or negatively in the development and implementation of decentralized management. To achieve these goals, with the concern and care for the look back is always the case, it was decided to search for both qualitative and some actions were necessary as to raise and examine documents, data showing the characteristics of the municipality, the administration and management. Based on my experience as manager in this process, I was already ahead of the municipal education secretary as the folder during the signing of the agreement and thereafter for one management, this work brings considerations, comparing the concepts and data collected by research, with a look back not only to the local level, but also for broader issues in a broader universe in which many of the phenomena are crucial for defining the local situation. The paper records the sequence of political and administrative acts in the context of educational reforms, bringing to debate the consequences of all this was for the municipality.